OCCURRENCE OF THE METABOLIC SYNDROME AND ITS EFFECT ON CARDIOVASCULAR RISK IN PATIENTS WITH GOUT - I. I. Polskaya; I. M. Marusenko; T. I. Kulagina; N. N. Vezikova (Рациональная фармакотерапия в кардиологии)
Aim. To study the prevalence of metabolic syndrome (MS) and total risk of cardiovascular diseases (CVD) in patients with gout depending on the presence of MS.Material and methods. 56 patients (aged 53.3±10.9 years; men 82%) with verified primary chronic gout [median disease duration 5.7 (2.0-8.5) years] and MS (the main group) were included into the study. The control group included 30 patients (aged 55.3±12.5 years; men 73.3%) with MS without gout and other inflammatory diseases. The following parameters were evaluated in all patients: MS characteristics, serum uric acid, creatinine, fasting glucose, total cholesterol, triglycerides, high density lipoprotein cholesterol (HDL cholesterol), low density lipoprotein cholesterol (LDL cholesterol), and high-sensitivity C-reactive protein. The total risk of CVD was calculated by the SCORE and PROCAM scales.Results. The incidence of arterial hypertension and hypertriglyceridemia was similar in the compared groups of patients with MS regardless of the presence of gout (p<0.001). Reduction in HDL cholesterol level was more typical for patients in the main group compared to patients with isolated MS (50% vs 23.3%; p<0.01). The total CVD risk was significantly higher in the patients of the main group compared to the patients with isolated MS [SCORE: 7.05 (3.84-9.03) vs 2.73 (1.71-4.97), p<0.01; PROCAM: 13.2 (6.55-23.0) vs 11.75 (7.0-17.5), p<0.05]. The strongest positive associations were found between the risk values on the PROCAM scale and the uric acid levels in the patients of both compared groups: correlation coefficients 0.13 and 0.25 in the patients of the main group and in patients with isolated MS, respectively.Conclusion. A high prevalence of the main risk factors in patients with gout was revealed. Serum levels of total cholesterol, LDL-C cholesterol and triglycerides made the main contribution to the increase in CVD risk according to SCORE and PROCAM scales. A higher CVD risk on the SCORE scale was found in patients with gout in combination with MS compared to patients with isolated MS (p<0.01). This fact indicates that namely a complex of metabolic disorders, developing both in gout and in MS, provides increase in the total CVD risk.